Comparison of active drag using the MRT-method and the MAD-system in front crawl swimming - Narita, K.; Ogita, F.; Nakashima, M.; Takagi, H. (Proceedings, 2018)
The purpose of this study was to compare the active drag values estimated by the MRT-method and the MAD-system. Six male competitive swimmers participated in this study and performed front crawl with arms only condition. The drag was compared at six-staged velocities ranged from 0.9 to 1.4 m/s between MRT-method and MAD-system. The drag estimated by MRT-method showed larger values than that obtained using MAD-system at each velocity (MRT-method/MAD-system: 119% at 1.0 m/s; 133% at 1.2 m/s; 147% at 1.4 m/s). In addition, the stroke length in MRT-method condition decreased with swimming velocity being increased, while that in MAD-system condition was constant. Therefore, swimmers had to increase their stroke frequency in MRT-method condition in order to achieve the same swimming velocities as MAD-system condition, especially at high velocities. It was concluded that the difference in the way of exerting propulsion between MAD-system and MRT-method influenced the active drag which were estimated in two methods